Effects of Delay in Multi-Agent Consensus and Oscillator Synchronization. - Papachristodoulou, A; Jadbabaie, A; Münz, U (2010)
The coordinated motion of multi-agent systems and oscillator synchronization are two important examples of networked control systems. In this technical note, we consider what effect multiple, non-commensurate (heterogeneous) communication delays can have on the consensus properties of large-scale multi-agent systems endowed with nonlinear dynamics. We show that the structure of the delayed dynamics allows functionality to be retained for arbitrary communication delays, even for switching topologies under certain connectivity conditions. The results are extended to the related problem of oscillator synchronization. © 2006 IEEE.